Utilizing Plant Synthetic Biology to Improve Human Health and Wellness - Barnum, Collin R.; Endelman, Benjamin J.; Shih, Patrick M. (Frontiers in Plant Science, 2021)
Plant synthetic biology is a rapidly developing field of research with the potential to revolutionize the way we eat as well as the way we treat and prevent human diseases. The World Health Organization has identified that 70% of preventable chronic diseases – including heart disease, diabetes and cancer – could be alleviated or prevented with a proper healthy diet. Unfortunately, lack of access to affordable fresh produce limits the intake of essential plant-derived nutrients. The rapidly evolving field of plant synthetic biology offers the ability to capitalize on the inventive chemistry of plants by transferring metabolic pathways that create natural, health-enhancing compounds to far more tenable crop species, increasing nutrient accessibility and affordability. Plant synthetic biology also provides methods to produce complex pharmaceuticals in well-studied plant systems, thus reducing our reliance on extracting compounds from native plants that are difficult to cultivate or suffer from unpredictable yields. In this review, we discuss 1) the potential of plant synthetic biology to improve human health through the enhancement of crops’ nutritional and nutraceutical properties and 2) the use of plants as platforms for the development and extraction of natural and new-to-nature therapeutic compounds. Plant synthetic biology may play a critical role as an alternative to traditional pharmaceutical production, which has the potential to reduce costs and increase the availability of necessary nutrients and drugs.